2002
DOI: 10.1164/rccm.2105118
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Hypertrophy and Abnormal Ventricular Geometry in Children and Adolescents with Obstructive Sleep Apnea

Abstract: Obstructive sleep apnea (OSA) has been shown to be an independent risk factor for cardiovascular disease in adults. However, there are severe limitations in the extent to which the cardiovascular consequences of OSA are being studied in children. To investigate the echocardiographic changes in children with OSA, right and left ventricular (RV, LV) dimensions and LV mass index and geometry were measured in 28 children with OSA and 19 children with primary snoring (PS). The study showed that LV mass index and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
232
1
22

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 407 publications
(261 citation statements)
references
References 36 publications
6
232
1
22
Order By: Relevance
“…This enlargement of the RV has also been observed in other studies, [13][14][15][16][17] although not with adjustment for the weight and height of each child.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This enlargement of the RV has also been observed in other studies, [13][14][15][16][17] although not with adjustment for the weight and height of each child.…”
Section: Discussionsupporting
confidence: 83%
“…16 The severity of obstructive respiratory events during sleep, expressed by the more elevated rates of apnea and hypopnea, suggest that they are directly correlated with LV abnormalities. 17 There is sufficient pathophysiologic evidence to allow for the suspicion that children with UA obstruction during sleep exhibit structural and functional cardiac abnormalities, notably of the right ventricle.…”
Section: Introductionmentioning
confidence: 99%
“…Immediate consequences of OSAS are sleep fragmentation, arousal, poor school/job performance, irritability, intermittent hypercapnia and hypoxemia, nocturnal hypertension and marked changes in autonomic control of the cardiovascular system. 88 The long-term consequences of OSAS include sustained daytime and nocturnal hypertension, 89,90 cor pulmonale, left ventricular hypertrophy 91 and increased cardiovascular and cerebrovascular morbidity and mortality. 92 Indeed, cross-sectional results from the Sleep Heart Health Study showed a strong association between OSAS, heart failure and stroke.…”
Section: Cardiovascular Risksmentioning
confidence: 99%
“…O aumento de VD tem sido observado em outros estudos [13][14][15][16][17] , embora não ajustado para peso e altura de cada criança.…”
Section: Segundo Steiner and Straunerunclassified
“…A cirurgia de adenotonsilectomia também resultou em melhora dos parâmetros de fluxo pulmonar e de área de VD em crianças com hipertensão pulmonar, relacionada à obstrução das VAS 16 . A gravidade de eventos respiratórios obstrutivos no sono, expressa pelo índice de apnéia e hipopnéia mais elevado, sugere estar correlacionada diretamente com alterações em VE 17 .…”
Section: Introductionunclassified